Finite element analysis of office building steel structure by using ANSYS - Fathin Nur Ammalina, Norhasim (2018)
Frame is one of the important elements of this structure. Unfit or improper design can lead to the failure of a structure. The warehouse steel frame was analyzed by manual calculation and also design in ANSYSsoftware. There are several, methods can be used to analyses the behavior of steel office building frame. However, among all these methods, finite element method and probabilistic method will be a very effective method to obtain the strength and the behavior of steel structure. This analysis is to determine the behavior frame design for the office building structure. This research will mainly focus on the steel frame of office building structure. The yield strength of steel jacket that used is 500N/mm2, which is the strongest steel. The value for the input variables are generated randomly by using Monte Carlo Simulation or as prescribed samples using Response Surface Methods. 1000 Simulations had been made to make sure the analysis is more precise and accurate. Here, the study were conducted to prove that a steel warehouse under the existence of randomness and uncertainty can be analyzed by apply probabilistic finite element analysis using ANSYS.